2016
DOI: 10.1007/s00268-016-3508-z
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Primary Spontaneous Pneumothorax is Common Following Chest Tube and Conservative Treatment

Abstract: Primary spontaneous pneumothorax in younger patients with their first episode had a much higher recurrence rate than previously reported. Every doctor who treats patients with primary spontaneous pneumothorax should be aware and patients informed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
3
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 38 publications
5
53
3
4
Order By: Relevance
“…Smoking is thus often presented as a risk factor for recurrence [3, 15]. Even though recurrence seems to occur earlier in smokers [9], we failed to find a significant relation between smoking and recurrence in our study, as in other studies [9, 13]. Furthermore, smokers could have a significant reduced risk of recurrence compared to nonsmokers [13].…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Smoking is thus often presented as a risk factor for recurrence [3, 15]. Even though recurrence seems to occur earlier in smokers [9], we failed to find a significant relation between smoking and recurrence in our study, as in other studies [9, 13]. Furthermore, smokers could have a significant reduced risk of recurrence compared to nonsmokers [13].…”
Section: Discussioncontrasting
confidence: 72%
“…Even though recurrence seems to occur earlier in smokers [9], we failed to find a significant relation between smoking and recurrence in our study, as in other studies [9, 13]. Furthermore, smokers could have a significant reduced risk of recurrence compared to nonsmokers [13]. An association between the use of cannabis and pneumothorax has been suggested in previous studies [1, 16–18], but no studies have explored the link between cannabis use and PSP recurrence.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…In a prospective randomized study, Noppen et al [34] observed a recurrence rate of 26% one year after aspiration, and a recurrence rate of 27.3% after drainage therapy in the same time period. A recent Danish prospective cohort study [35] showed a recurrence rate in PSP of 54% after drainage therapy, the median observation time here was 3.6 years.…”
Section: Recurrence Ratementioning
confidence: 54%